The use of a surface active agent in the protection of a fusion protein during bioprocessing. Issue 11 (8th September 2018) - Blas, Peter; Tolner, Berend; Ward, John; Chester, Kerry; Hoare, Mike
Abstract: The bioprocessing of a fusion protein is characterised by low yields and at a series of recovery and purification stages that leads to an overall 90% loss. Much of this apparent loss is due to the denaturation of a protein, missing a vital affinity ligand. However, there is evidence of the protection of degradation products which occurs in the presence of shear plus air/liquid interfaces. This study seeks out to characterise the loss and use ultra‐scale‐down studies to predict its occurrence and hence shows these may be diminished by the use of protective reagents such as Pluronic F68. Abstract : The bioprocessing of a fusion protein is characterised by low yields and at a series of recovery and purification stages that leads to an overall 90% loss. Much of this apparent loss is due to the denaturation of a protein, missing a vital affinity ligand.